Safety profile of lasmiditan in patients with migraine in an Asian population. Issue 1 (2nd January 2023) - Hirata, Koichi; Matsumori, Yasuhiko; Tanji, Yuka; Khanna, Rashna; Ozeki, Akichika; Komori, Mika
ABSTRACT: Background: MONONOFU, a multicenter, randomized, double-blind, placebo-controlled phase 2 study of Japanese patients with migraine, was pivotal for lasmiditan approval in Japan. However, treatment-emergent adverse events (TEAEs) were more common than in global studies. A detailed safety profile would assist patient management. Research design and methods: Safety assessments in MONONOFU included specific terms reported, frequency, severity, time to onset, duration, TEAE management, common TEAE risk factors, and TEAE–efficacy associations. Results: Of 846 participants, 691 were assessed for safety. The proportion of participants reporting ≥1 TEAE was 23.4% with placebo and 70.9% with lasmiditan; 87.3% of TEAEs with lasmiditan were mild. The most frequent TEAEs with lasmiditan, dizziness (39.4%) and somnolence (19.3%), started ≤1 hour postdose (median durations: 2.5 and 3.3 hours, respectively). Higher lasmiditan dose, but not patient factors including body size, was identified as a clinically meaningful predictor of dizziness and somnolence. There were no adverse consequences of neurological TEAEs, which did not appear to adversely affect lasmiditan efficacy. Conclusions: In the MONONOFU study, TEAEs appeared typically mild, transient, and self-limiting. Lasmiditan may represent a useful and well-tolerated acute treatment option for smaller (body mass index <30 kg/m 2 ) patients and Asian patients with migraine. GRAPHICAL ABSTRACT: uf0001